Influência de parâmetros abióticos na estruturação da taxocenose suprabêntica de peixes em cinco áreas de costão rochoso em Arraial do Cabo, RJ - Vianna, Marcelo (1992)
The composition and distribution as a function of environment factors were studied on a suprabentic fishes in the rocky coastal area of Arraial assemblace of do Cabo. Were selected the following areas: Porto, Anjos and Forno at the Arraial do Cabo Bay and Alcalis and Prainha at the "Saco da Prainha". The ichthyofauna struture data and hydrographic factors were obtained during the summer of 1991. The bentic substrate composition was characterized between August and September of 1991. The physiographic data was recorded and classified within these stations comparatively considering the wave strokes, the degree of embayment and the average water depth at the studied area. The substrate was quantified, at two different depths leveis, using the line transect technique. Nine parameters on the water quality were measured. The visual census per area and gathering of testimony specimens were used to record fishes and their abundance. The physiographyc factors were analyzed by clusterina and showed two different groups: one with Anjos, Prainha and Forno and the other with Porto and Alcalis. Within the benthos eight types of components were related and the indexs of diversity was applied, demontrating that Porto area has the smaller values and the Prainha has the highest ones. Cluster analysis were obtained per stations, and the dendrosram showed two groups, the first group with Forno, AnJos and Prainha and the second with Porto and Alcalis. Good conditions in the water were observed ln the stations. and the application of discrimnant analsis did not indicate the presence of significant difference in the water in the stations or significance amona the parameters studied and the distribution of bentic and fishes. In conclusion, in the studied areas the differences in assemblage of fishes are probably more influenced by physio-geographyc variations than by bentic compositions or the hydrographic factors.